King Zedekiah’s release of slaves for the strategic harmony of a besieged Jerusalem (Jer 34) - Scolnic, Benjamin E. (Zeitschrift für die alttestamentliche Wissenschaft, 2023)
King Zedekiah of Judah’s covenant to release Hebrew slaves during the siege of Jerusalem by the Babylonians in 588/587 and Jeremiah’s idealistic denunciation of the reclaiming of those slaves in Jer 34 has been the subject of interesting scholarly debate. For all the proposed foreign and intra-Biblical parallels, the policy was purely pragmatic and can be understood as a recognizable strategy from ancient texts that recommend procedures during a siege. Therefore when the siege is temporarily lifted, the policy is reversed.
Keywords: Jeremiah; Jerusalem; Sieges; Slavery; Warfare; dept.jst